(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
This paper provides insight into the rapid transition experienced by the students and staff who, before COVID-19 mandated shutdowns, were part of a blended instructional format for their classes. The students reported general satisfaction with the online transition while expressing reservations about the loss of personal interaction and concerns about inabilities to engage field experiences deemed critical to completion of the program.